Religiusitas, Kontrol Diri dan Kenakalan Remaja - Aviyah, Evi; Farid, Muhammad (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. This study aimed with determine the correlation between religiusity and self-control with juvenile tendencies. The subjects were 100 students both from SMA Negeri 1 Bancar and SMA Negeri 1 Jatirogo. Sampling technique used in this study was purposive sampling. Data collection instrument used in this study were juvenile delinquency scale , the scale of religiosity and self-control scale refers to the making according to a Likert scale. The results of data analysis using regression Anareg get the F = 17.954 with  p = 0.00 (p < 0.01). Religiusity and self-control variables simultaneously and significantly correlated with delinquency. Partially, it was found the value of t Regression between religiusity and juvenile delinquency  = -3.632, and r = -0.346 partial, with p = 0.000             (p <  0.01), this means that there is a significant negative relationship between religiusity and juvenile delinquency. Partial Test also find the value of t regression between the variables of self-control with juvenile delinquency = -2.737 and         r = -0.268  with a partial p = 0.007 (p < 0.01), this means that there is a significant negative relationship between self-control with juvenile delinquency. Effective contribution of religiusity and self-control variables was 27 % (R square = 0.270).Keywords: Religiusity, Self-Control, Juvenile Delinquency.